Analisis Kinerja Keuangan Berdasarkan Rasio Profitabilitas : Pada PT Dealova Indonesia - Vita Rizaqoh; Asep Suherman (Prisani Cendekia, 2023)
Financial indicators are analytical tools that aim to measure the extent to which a company carries out its activities in accordance with the rules of financial implementation. The purpose of this research is to evaluate and measure the financial performance of PT. Delova Indonesia, the company is a competent company with the ability to generate profits. The collection of data in this study was quoted directly from the financial reports of PT. Dilova Indonesia 2018 to 2020. This research uses quantitative analysis. Based on the research results it is known that the financial indicators of PT. Delova Indonesia is in a